Role of a tripartite efflux pump in the symbiosis between Sinorhizobium meliloti and leguminous plants - Marques, Andreia Filipa Tomás, 1987- (2012)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2011